2014
DOI: 10.14748/bmr.v25.1042
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of the endothelin system in colorectal cancer

Abstract: Endothelin system members including endothelin-1, endothelin-2, endothelin-3, endothelin receptors, and

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 71 publications
(95 reference statements)
0
2
0
Order By: Relevance
“…Huang, Wu (66) demonstrated that miR-485 directly suppresses EDNRA expression, thereby impeding the progression of esophageal squamous cell. In colon cancer, EDNRA was associated with advanced tumor grade and stage [67,68].Moreover, it has been that GNA14 has tumor promoting role in colon [69] and epithelial cell cancer [70]. Interesting, Oshima, Ishikawa (71) demonstrated that miR-485 inhibits GNA14 expression, attenuating the proliferation and metastasis of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…Huang, Wu (66) demonstrated that miR-485 directly suppresses EDNRA expression, thereby impeding the progression of esophageal squamous cell. In colon cancer, EDNRA was associated with advanced tumor grade and stage [67,68].Moreover, it has been that GNA14 has tumor promoting role in colon [69] and epithelial cell cancer [70]. Interesting, Oshima, Ishikawa (71) demonstrated that miR-485 inhibits GNA14 expression, attenuating the proliferation and metastasis of gastric cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…The endothelin system consists of endothelin-1 (EDN-1), endothelin-2 (EDN-2), endothelin-3 (EDN-3), the G-proteincoupled receptors, endothelin receptor type A (EDNRA) and endothelin receptor type B (EDNRB), endothelin converting enzyme 1 (ECE1), and endothelin converting enzyme 2 (ECE2) (Wang et al, 2013;Mahdi et al, 2014). Endothelin-1 has an enhancing effect on cancer cell proliferation, survival, invasion, and migration; it also has an effect on cancer stroma cells such as fibroblasts [proliferation, migration, contraction, extracellular matrix (ECM) remodeling], macrophages (chemo-attraction, ECM remodeling), and endothelial cells (proliferation, angiogenesis) (Bhalla et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, loss of EDN2 or EDN3 in rat colon mucosa indicates their use as early marker for colon cancer. Furthermore, increased EDNRA expression in CRC patients is correlated with increased tumor grade and reduced patient survival (Mahdi et al, 2014). Therefore, endothelin system members are considered as major regulating factors in cancer cell biology and cancer microenvironment and modulation of this gene system in cancer progression is an interesting topic of research.…”
Section: Discussionmentioning
confidence: 99%